The Linguistic Potential of the COVID-19 Lexeme in English and Slovak (A corpus-based study) - Lacková, Marta (Research in Language, 2025)
The aim of this article is to investigate the morphological and lexicosemantic traits of the COVID-19 lexeme as demonstrated in the framework of the English Web 2021 (enTenTen21) and the Slovak National Corpus (web-6.0). The exploration of the word-formation potential of the lexeme is carried out, too. A preliminary step of the research procedure is to recognize recurring patterns in which the studied lexical unit occurs so that we could inquiry into its functions in the given discourse. To achieve its goals, the combination of the lexical analysis and corpus analysis methods is employed. The findings of this study reveal that the lexeme COVID-19 entered all spheres of communication within both the studied languages. Furthermore, it has been adapted to their morphological and lexical systems and can access regular word-formation processes existing in them.